State of the art on toxicological mechanisms of metal and metal oxide nanoparticles and strategies to reduce toxicological risks - García-Torra, Victor (2021)
Metal nanoparticles have been extensively investigated for different types of pharmaceutical applications. However, their use has raised some concerns about their toxicity involving the increase of reactive oxygen species causing cellular apoptosis. Therefore, in this review we summarize the most relevant toxicity mechanisms of gold, silver, copper and copper oxide nanoparticles as well as production methods of metal nanoparticles. Parameters involved in their toxicity such as size, surface charge and concentration are also highlighted. Moreover, a critical revision of the literature about the strategies used to reduce the toxicity of this type of nanoparticles is carried out throughout the review. Additionally, surface modifications using different coating strategies, nanoparticles targeting and morphology modifications are deeply explained.